2015
DOI: 10.1080/15533174.2013.843545
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Study of Transition Metal Ion Catalyzed Vilsmeier–Haack Cyclization and Formylation Reactions with Acetanilides

Abstract: Vilsmeier-Haack reactions (VHR) with acetanilides afforded 2-chloro 3-formyl quinoline derivatives. The reactions obeyed second order kinetics with a first order dependence on VHR as well as acetanilide. Significant rate enhancements were observed when transition metal ions such as Cu(II), Ni(II), Co(II), and Cd(II) were used as catalysts in these reactions. The kinetic results in transition metal ion catalyzed reactions coupled with uv-visible spectrophotometric observations substantiated the participation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…5,49,[51][52][53][54][55][56] The better method for the synthesis of quinolines depending on the nature of the substituents in order to obtain the best yields. Aneesa et al, 57 have reported the effect of transition metal ions such as Cu(II), Ni(II), Co(II), and Cd(II) on the synthesis of quinolines through the Vilsmeier reagent with acetanilides 15. Vilsmeier reagent was prepared by reaction of thionyl chloride (SOCl 2 ) or phosphorus oxychloride (POCl 3 ) with N,N-dimethylformamide (DMF).…”
Section: Synthesis Of 2-chloro-3-formylquinolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,49,[51][52][53][54][55][56] The better method for the synthesis of quinolines depending on the nature of the substituents in order to obtain the best yields. Aneesa et al, 57 have reported the effect of transition metal ions such as Cu(II), Ni(II), Co(II), and Cd(II) on the synthesis of quinolines through the Vilsmeier reagent with acetanilides 15. Vilsmeier reagent was prepared by reaction of thionyl chloride (SOCl 2 ) or phosphorus oxychloride (POCl 3 ) with N,N-dimethylformamide (DMF).…”
Section: Synthesis Of 2-chloro-3-formylquinolinesmentioning
confidence: 99%
“…Aneesa et al , 57 have reported the effect of transition metal ions such as Cu( ii ), Ni( ii ), Co( ii ), and Cd( ii ) on the synthesis of quinolines through the Vilsmeier reagent with acetanilides 15. Vilsmeier reagent was prepared by reaction of thionyl chloride (SOCl 2 ) or phosphorus oxychloride (POCl 3 ) with N , N -dimethylformamide (DMF).…”
Section: Synthesis Of Quinoline Ring Systemsmentioning
confidence: 99%